Allergen immunotherapy for asthma prevention: A systematic review and meta‐analysis of randomized and non‐randomized controlled studies - Farraia, Mariana; Paciência, Inês; Castro Mendes, Francisca; Cavaleiro Rufo, João; Shamji, Mohamed; Agache, Ioana; Moreira, André (Allergy (Copenhagen), 2022)
Background Allergen immunotherapy (AIT) is a disease‐modifying treatment for IgE‐mediated diseases. Randomized controlled trials (RCTs) support AIT's potential role in asthma prevention but evidence from non‐randomized studies of interventions (NRSI) and longitudinal observational studies has been poorly addressed. Therefore, we aimed to conduct a systematic review and meta‐analysis to assess clinical data from all study types to evaluate quantitatively the preventive role of AIT in asthma onset. Methods We search three databases. Studies were screened, selected and evaluated for quality using risk‐of‐bias (ROB) tools. Data were descriptively summarized and meta‐analysed using random effects. We performed a sensitivity, influence and subgroup analyses. Publication bias and heterogeneity were assessed. Results From the 4549 identified studies, 24 (12 RCTs and 12 NRSI) were included in the qualitative synthesis and 18 underwent meta‐analysis. One study was at low ROB, seven had moderate ROB, and 15 were proven of high ROB. Random‐effects analysis showed a significant decrease in the risk of developing asthma following AIT by 25% (RR, 95% CI: 0.75, 0.64–0.88). This effect was not significant in the sensitivity analysis. Publication bias raised concerns, together with the moderate heterogeneity between studies (I2 = 58%). Subgroup analysis showed a remarkable preventive effect of AIT in children (RR, 95% CI: 0.71, 0.53–0.96), when completing 3 years of therapy (RR, 95% CI: 0.64, 0.47–0.88), and in mono‐sensitized patients (RR, 95% CI: 0.49, 0.39–0.61). Conclusions Our findings support a possible preventive effect of AIT in asthma onset and suggest an enhanced effect when administered in children, mono‐sensitized, and for at least 3 years, independently of allergen type.